MEL APP CGIAR Initiative on Agroecology - Espinosa Gutierrez, Herlin Rodolfo; Guevara Valencia, Edward Dario; Staiger Rivas, Simone (2022)
The MELIA - Agroecology - application allows the management (generation and upload of templates and download of massive information) of the key performance indicators of the CGIAR initiative on Agroecoolgy. The platform was implemented so that administrator users can create new indicators. The application provides a dashboard that allows the visualization of basic graphs with the information that is collected online. A basic registry is necessary to assign permissions according to the user's role. Finally, the application was designed so that at a given moment the implementation of other functionalities or modules is allowed.